DRAFT COMPREHENSIVE ASSESSMENT OF COASTAL RECREATIONAL AREAS ON ECOLOG I CAL AND HYGIENIC CHARACTERISTICS - O.L. Mitina (Bogomolets National Medical University, 2015)
Summary: The article is devoted to the problem of the sanitary ecological state of recreational areas. An author on the basis of empiric research's result was developed the draft of comprehensive assessment of the sanitary ecological state of coastal recreational areas. This scheme proposes an analysis of recreational loading and recreants' opinion poll on the issue of the environmental quality and the study of the most important indicators of sea water, sediment, contamination of beach sand by household waste and staging experiments by bioindication with typical representatives of coastal recreational areas. Statistical analysis of the results showed that the most pronounced differences in terms of total suspended solids and solid waste in the area of the beach Omega in compare with the beaches of the north part of Sevastopol, whereas the most pronounced correlation between the indices of the total suspended solids and content of sea water's oxygen (r = -0,965), as well as the total suspended solids and the amount of garbage on the beach (r = 0,753). Between the recreational load and the amount of municipal solid waste has been identified the feedback (r = -0,702). We can assume that this trend is associated with the better cleaning of popular beaches and municipal protection of less visiting areas.